1985
DOI: 10.1093/nar/13.14.5269
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of DNA polymerase from the archaebacteriumSulfolobus acidocaldarius

Abstract: DNA polymerase has been purified about 25,000-fold from the thermoacidophilic archaebacterium Sulfolobus acidocaldarius. On SDS-PAGE the enzyme was observed to have a molecular weight of 100 kDa and to be about 90% pure. The native molecular weight was 108 kDa indicating that the enzyme is composed of a single polypeptide. Activity gel analysis showed an active polypeptide of about 100 kDa. Under conditions promoting proteolysis this polypeptide was degraded to a slightly smaller form of 98 kDa. The enzyme has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…nt, nucleotides. Except for the enzyme from S. acidocaldarius, for which conflicting results have been reported (13,21), all (unmodified) archaeal polymerases studied exhibit 3Ј-5Ј exonuclease activity (28). We have also detected a very weak 5Ј-3Ј exonuclease activity of the C. symbiosum polymerase on double-stranded DNA templates.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…nt, nucleotides. Except for the enzyme from S. acidocaldarius, for which conflicting results have been reported (13,21), all (unmodified) archaeal polymerases studied exhibit 3Ј-5Ј exonuclease activity (28). We have also detected a very weak 5Ј-3Ј exonuclease activity of the C. symbiosum polymerase on double-stranded DNA templates.…”
Section: Discussionmentioning
confidence: 53%
“…2). The protein reported here is most closely related to this second, crenarchaeotal group, e.g., to the polymerases from Sulfolobus acidocaldarius and S. solfataricus that have been purified as the major polymerization activity from these thermophiles (13,21) and to one of the two polymerases of P. occultum (38).…”
mentioning
confidence: 85%
“…The most common indicator of the presence of a eukaryotic-like DNA polymerase was sensitivity to aphidicolin, a fungal metabolite which inhibits eukaryotic DNA replication by allosterically binding to the replicative DNA polymerases (45). By using aphidicolin sensitivity as an indicator, S. acidocaldarius and S. solfataricus were found to possess a eukaryoticlike DNA polymerase activity as well as an unclassified aphidicolin-resistant DNA polymerase activity (14,29,35,41,49). Sequencing of the gene corresponding to the aphidicolin-sensitive activity from S. solfataricus MT4 confirmed that this DNA polymerase was a family B homolog more similar to eukaryotic than to eubacterial homologs (38).…”
Section: Discussionmentioning
confidence: 99%
“…Aphidicolin-sensitive DNA polymerases were subsequently purified from halophilic, methanogenic, and some thermophilic archaea, suggesting that, like eukaryotes and unlike eubacteria, archaea use an aphidicolin-sensitive DNA polymerase for DNA replication (summarized in reference 20). However, not all archaea demonstrate a sensitivity to aphidicolin, and aphidicolin-resistant DNA polymerases have recently been isolated and biochemically characterized from archaea that had been shown to also contain aphidicolin-sensitive DNA enzymes (14,25,29,35,48,49). Sequencing of the genes for several aphidicolin-sensitive and one aphidicolin-resistant DNA polymerase revealed that these DNA polymerases are all homologous to family B DNA polymerases from eubacteria and eukaryotes (34,38,48,49) and more similar at the amino acid level to eukaryotic homologs.…”
mentioning
confidence: 99%
“…Three enzymes, PolB1, PolB2 and PolB3, belong to family B of DNA polymerases (She et al, 2001b). The replicative polymerase B1 has been most intensively studied (Klimczak et al, 1985;Rossi et al, 1986;Bukhrashvili et al, 1989;Chinchaladze et al, 1989;Elie et al, 1989; reviewed by Böhlke et al, 2002). Sulfolobus possesses also a DNA polymerase belonging to the Y family, which apparently is specialized in the replication of aberrant DNA templates and is able to bypass certain DNA lesions in an error-free manner (Kulaeva et al, 1996;Boudsocq et al, 2001;Gruz et al, 2001;Kokoshka et al, 2002;Potapova et al, 2002).…”
Section: Uridine-5′-monophosphatementioning
confidence: 99%